EVALUATION OF LOCAL GOVERNMENT PROPERTY ADMINISTRATION POLICIES - Yaya Mulyana (GoAcademica Research dan Publishing, 2023)
The government's success in effectively managing its operations is closely tied to the outcomes of the policies it implements. Law Number 23 of 2014 aims to expedite the enhancement of societal well-being by bettering services, promoting empowerment and community involvement, and enhancing regional competitiveness. This is done while upholding democratic principles, fairness, justice, regional distinctiveness, as well as the efficiency and effectiveness of regional governance. Enhancing the relationship between central and regional governments, acknowledging the diverse potentials of various regions, and addressing competitive opportunities and challenges can further refine regional government administration. This research employs a qualitative descriptive approach, focusing on capturing current, genuine, and practical phenomena. Among the pivotal components of effective governance and public service lies the proper management and responsible oversight of regional assets. Many assets are owned by a region, sometimes in terms of administration, they receive less attention in the field of business administration, which is a must for state administrators to realize good and clean governance.